2018
DOI: 10.1002/adom.201800548
|View full text |Cite
|
Sign up to set email alerts
|

Simple, Flexible, and Ultrastable Surface Enhanced Raman Scattering Substrate Based on Plasmonic Nanopaper Decorated with Graphene Oxide

Abstract: Surface enhanced Raman spectroscopy (SERS) is becoming a paramount analytical mechanism in nanotechnology and biological/chemical detection. However, fabrication of highly sensitive SERS substrates often involves expensive and time‐consuming procedures and the resulting materials require careful handling. Herein, a simple‐to‐manufacture, highly sensitive, and easy‐to‐handle SERS substrate enabled by plasmonic nanopaper decorated with graphene oxide flakes is reported. Owing to the physicochemical properties ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Among them, the in situ SERS detection based on the flexible substrates is considered as the most promising approach, which is performed by first conformally attaching the flexible SERS substrates onto objective surfaces of interest, followed by the excitation of incident photons and collection of Raman signals from the back side of the SERS substrates. Until now, a diversity of flexible substrates have been applied for in‐situ SERS detection, such as PDMS, PMMA, polyethylene terephthalate (PET), polyethylene (PE), poly(vinylpyrrolidone) (PVP), paper, adhesive tape, as well as nanowires . The conventional methods to prepare active nanostructures on flexible and transparent substrates rely on depositing nanoparticles by physical or chemical routes.…”
Section: Various Categories Of Flexible Sensorsmentioning
confidence: 99%
“…Among them, the in situ SERS detection based on the flexible substrates is considered as the most promising approach, which is performed by first conformally attaching the flexible SERS substrates onto objective surfaces of interest, followed by the excitation of incident photons and collection of Raman signals from the back side of the SERS substrates. Until now, a diversity of flexible substrates have been applied for in‐situ SERS detection, such as PDMS, PMMA, polyethylene terephthalate (PET), polyethylene (PE), poly(vinylpyrrolidone) (PVP), paper, adhesive tape, as well as nanowires . The conventional methods to prepare active nanostructures on flexible and transparent substrates rely on depositing nanoparticles by physical or chemical routes.…”
Section: Various Categories Of Flexible Sensorsmentioning
confidence: 99%
“…[100] Interestingly, Xiong et al discussed that the thickness of GO-coated gold surfaces with a GO layer thickness of around hundreds of nanometers led to a significant improvement in SPR sensitivity given a modulation in the refractive index sensitivity caused by the studied GO coating. [116,117] GO has also been reported to endow SERS substrates with ultrastable analytical behavior, thus enabling the analysis of the same Raman signature throughout tens of days. [101] It is well known that Raman spectroscopy facilitates the determination of bio/molecules via their highly specific Raman scattering.…”
Section: Go In Label-free Optical Biosensingmentioning
confidence: 99%
“…They also concluded that the SPR sensitivity was observed to be proportional to the thickness of the explored GO coating. [117] Notably, the literature describes particular SERS applications of composites-incorporating GO in several fields, [31,74] including bio-imaging, [117,118] biomarkers detection, [119][120][121] bacteria determination, [121] pesticides monitoring, [122] and food analysis among others. [102] In this regard, surface-enhanced Raman spectroscopy (SERS) can also be exploited as a powerful label-free bioanalytical platform based on vibrational spectroscopy.…”
Section: Go In Label-free Optical Biosensingmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of their excellent capture efficiency and limit of detection (LOD), complex post processes, including cell release, for investigating genetic information of tumor cells hinder its clinical application due to the low cell viability. In order to enable molecular characterization and cell analysis without post processes, SERS spectroscopy employing nanogap-rich metal nanoparticles-based structures can be an effective analytic tool [ 32 , 33 ]. Although SERS spectroscopy can investigate CTCs directly, few researches have reported the capture efficiency at the same time.…”
Section: Introductionmentioning
confidence: 99%